Maps with Vanishing Denominator and Their Applications - Pecora, Nicolò; Tramontana, Fabio (Frontiers in Applied Mathematics and Statistics, 2016)
We survey the theoretical findings and a set of applications in several different fields concerning two-dimensional maps characterized by a vanishing denominator. This family of maps, and the related dynamic properties, were originally brought to the attention of the researchers through their appearance in an economic application. Nowadays such maps have also been used in other research areas such as ecology or biology confirming a broader application of the theoretical results about plane maps with vanishing denominator to various research areas.